The G2/M transition - Medema, René (Henry Stewart Talks, 2009)
Cell Division, Cell fusion experiments, The cyclins and Cdks, Mitosis, Cyclin B1/Cdk1, Feedback loops in Cdk activation, Polo-like kinase-1, Checkpoints, Checkpoint recovery